2022
DOI: 10.3390/molecules27062006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the In Vitro Activity of Selected Porphyrins in Human Colorectal Cancer Cells

Abstract: Standard in vitro analyses determining the activity of different compounds included in the chemotherapy of colon cancer are currently insufficient. New ideas, such as photodynamic therapy (PDT), may bring tangible benefits. The aim of this study was to show that the biological activity of selected free-base and manganese (III) metallated porphyrins differs in the limitation of colon cancer cell growth in vitro. White light irradiation was also hypothesized to initiate a photodynamic effect on tested porphyrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…As opposed to the HT-29 cells, 5-FU did not cause a lowered cell proliferation on HDFs via CAN spectroscopy but remained constant ( Figure 3B ). The shorter doubling time of HT-29 cells ( Forgue-Lafitte et al, 1989 ; Frant et al, 2022 ) compared to HDFs ( Zhu et al, 2004 ; Endt et al, 2010 ; Rorteau et al, 2022 ) may lead to a higher 5-FU-uptake, resulting in stronger proliferation-reducing effects of drug treatment. However, the HDFs’ metabolic activity in the CCK-8 assay in the 5-FU-supplemented medium dropped after 24 h of exposure and stayed constant for the remaining time ( Figure 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to the HT-29 cells, 5-FU did not cause a lowered cell proliferation on HDFs via CAN spectroscopy but remained constant ( Figure 3B ). The shorter doubling time of HT-29 cells ( Forgue-Lafitte et al, 1989 ; Frant et al, 2022 ) compared to HDFs ( Zhu et al, 2004 ; Endt et al, 2010 ; Rorteau et al, 2022 ) may lead to a higher 5-FU-uptake, resulting in stronger proliferation-reducing effects of drug treatment. However, the HDFs’ metabolic activity in the CCK-8 assay in the 5-FU-supplemented medium dropped after 24 h of exposure and stayed constant for the remaining time ( Figure 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…However, cells absorbed the porphyrin [ 24 ]. Our previous study [ 25 ] indicated that the cytotoxic activity of manganese porphyrin was due to damage to the cell membrane. The evidence suggests that the porphyrin under investigation may not be entering the cell, but instead accumulating within the cell membrane or culture fluid.…”
Section: Discussionmentioning
confidence: 99%
“…During the incubation of cells with the porphyrins, culture plates were sealed with aluminum foil. Experiments were conducted in two separate conditions: no irradiation (during the entire experiment) and short exposure to white light (3 min) emitted by fluorescent lamps (Osram Lumilux Cool White, Wilmington, MA, USA) with a total power of 90 W and a photon flux density of 120 µmol/m 2 s, according to the method described by Buczek et al [ 59 ] and Frant et al [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these studies, coordination with palladium was not as advantageous as with platinum [139], and for porphyrin dyes complexed with copper, nickel, and zinc ions, the copper derivative showed the worst photodynamic effects [140]. In contrast to most research involving metalloporphyrins, Frant et al [142] conclude in their work that manganese-metalized porphyrin is, by itself, cytotoxic, while its free-base analog induces effects only when irradiated on colorectal cancer cells. N-heterocyclic carbene, gold, mesofunctionalized zinc, and palladium coordinated porphyrins prepared by Scoditti et al [143] showed no cumulative impact on the ISC rate, revealing that the introduction of metals at different porphyrin positions does not induce a synergistic effect.…”
Section: N-heterocyclic-bearing Dyes As Photodynamic Therapy Photosen...mentioning
confidence: 99%